Preservasi Digital Film “Yang Terlupakan” sebagai Media Dokumentasi Perjuangan Bangsa - Anggreanie, Delta Ira (Media Informasi, 2025)
This research explores the potential of digital preservation through local films, focusing on strengthening cultural identity and maintaining local history. This study is important because film is one of the most effective means to convey cultural values to current and future generations. This research uses a qualitative approach, using the movie “Yang Terlupakan” as the object of research. Data were collected through semi-structured interview method, as well as data enrichment through related documents and supporting literature sources. The data analysis in this study utilizes thematic analysis. The stages in this study involve understanding the data followed by careful identification processes. The results show that the movie “Yang Terlupakan” has the potential to strengthen cultural identity and maintain local history. The discussion explores the implications of these results in the context of cultural preservation and history learning through local films. This research concludes the importance of using local films for cultural preservation and historical learning. Digital preservation through films can be implemented in libraries and information institutions as a creative educational medium to foster historical literacy and youth nationalism. Future research is suggested to develop a more integrated preservation strategy and involve collaboration between youth, government, and society in preserving cultural heritage through modern media. Keywords: Digital preservation; Film; Rejodani monument; Nationalism; Youth